STUDI NUMERIK PENGARUH PENAMBAHAN GUIDE VANES TERHADAP KINERJA CIRCULAR ELBOW - Imam Santoso; Setyo Nugroho; Prima Dewi Permatasari (PROSIDING SNAST, 2018)
The use of curved pipes will cause a pressure drop that is greater than the straight pipe of the same length. This is because there is a large pressure difference between the outer wall and the inner wall, eventually blocking the flow of fluid in the pipe. Pressure drop (pressure drop) of this flow is caused by friction (friction loss), separation (separation) and secondary flow (secondary flow). One method that can reduce pressure on the 900 elbow with the guide vane. The test module is in the form of a circular elbow 900 with a radius ratio (rc / Dh) = 1.2217 without a guide vane and uses a variety of number of guide vane. Numerical research uses computational fluid dynamics (CFD) method using computational software ANSYS FLUENT 14.5 with ReDolds number 9.8x104 ReDh. Fluid in the form of air with an inlet speed is uniform. From the results of this study obtained pressure drop, contour preset coefficient, velocity vector and pathline to determine the fluid flow phenomenon passing through the circular elbow with the addition of one guide vane, two guide vane, three guide vane, and without guide vane as a reference the phenomenon of the addition of guide vanes . The addition of guide vane gives the effect of increasing pressure drop. The biggest increase in pressure drop was the addition of three guide vane with an increase of 45.54% compared to the reference. The magnitude of this pressure drop occurs due to an increase in fluid friction with guide vanes and vortices which block the mainflow in circular elbow.